Traitement psychosocial des désordres d'appétence et de dépendance au sein d'une population délinquante - Dumont, Florent; Vamos, Peter (Canadian Journal of Counselling and Psychotherapy, 2012)
Appetitive and addictive disorders in a delinquent population are grounded inpersonality and emotional problems. Long-term rehabilitation depends on changes taking place in that substrate. This article examines some of the perceptual biases and maladaptive attitudes of chemically dependent delinquents. Several principles fordeveloping treatment programs addressed to the remediation of those deficits are offered.